The extraordinary legal policy for Corruption Crimes in shifting the formulation of attempted crimes as perfect crimes. - Nina Zainab (Siber International Journal of Advanced Law (SIJAL), 2024)
The regulation of criminal acts of attempt is known in the Criminal Code, especially in article 53, which states "attempting to commit a crime will be subject to punishment if it is clear that there has been an initial act and the act is not completed not because of one's own will." In the concept of the Criminal Code, attempted action is an action that is declared to have not been completed because something was not completed because it was not the intention of the perpetrator. In the law on eradicating corruption, the concept of an offense or attempted criminal act is not recognized because every crime that occurs in connection with corruption will be considered completed or complete as long as there has been an initial act or act. This can be understood considering that the criminal act of corruption is a special criminal act whose mode changes and develops, is very neat, covert and organized. Often criminal acts of corruption begin with initial actions in the form of promises and agreements while observing the situation, then the implementation will be carried out later to disguise the act, which is why criminal acts like this are often difficult to catch if the Criminal Code concept of attempted criminal acts is used as a measure. Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 concerning the Eradication of Corruption contains several articles whose concept is different from the Criminal Code, where in eradicating corruption an initial action is deemed to have completed corruption. This research is normative research in which the author examines the collected library materials consisting of primary, secondary and tertiary legal materials followed by in-depth observations of the phenomena that occur. The data obtained is then processed systematically by carrying out grammatical interpretations that will be used in discussing existing problems. The results of the research show that there are differences in the concept of trials regulated in the Criminal Code and trials regulated in the Corruption Law, where in this law the element of initial action has proven that there has been an attempt or act of corruption, so that the criminal act/delict is considered complete and the perpetrator can convicted of committing a criminal act of corruption.